Economic analysis of a cosmetic initiative addressing stochastic aspects and risk quantification - Costa, Vinicius Braga Ferreira da; Valério, Victor Eduardo de Mello; Miranda, Rafael de Carvalho (Acta Scientiarum. Technology, 2023)
This paper evaluates the economic feasibility of a small/medium-scale cosmetic initiative in a typical Brazilian city. The Brazilian cosmetic sector is very promising for investors, particularly when e-commerce platforms are designed, as virtual sales are the new trend in the sector. Therefore, the required costs to implement an e-commerce platform are considered to guarantee demand for the factory´s productive capacity. While deterministic analysis might provide initial overviews of economic feasibility, there are inherent risks associated with manufacturing. These risks are likely to influence considerably the outcome of economic evaluation, hence, stochastic analysis is performed based on the software Oracle Crystal BallÂ®. The proposed approach guarantees an accurate and detailed evaluation, as well as solid conclusions regarding the economic feasibility of cosmetic initiatives in Brazil. Results show that such initiatives are highly profitable.